Relational aggression in adolescents with conduct disorder: sex differences and behavioral correlates - Ackermann, Katharina; Kirchner, Marietta; Bernhard, Anka; Martinelli, Anne; Anomitri, Chrysanthi; Baker, Rosalind; Baumann, Sarah; Dochnal, Roberta; Fernandez-Rivas, Aranzazu; Gonzalez-Madruga, Karen; Herpertz-Dahlmann, Beate; Hervas, Amaia; et al. (Journal of abnormal child psychology, 2019)
As most research on conduct disorder (CD) has been conducted on male participants, it has been suggested that female-specific symptoms may be underestimated based on current DSM-5 criteria. In particular, relational aggression, i.e. the hurtful, often indirect, manipulation of relationships with the intention of damaging the other’s social position, has been proposed as a characteristic of CD that is more common in females. In addition, sex-specific studies on correlates of relational aggressive behavior are lacking. Relational aggression may be strongly related to the correlates of proactive aggression, namely low affective empathy, and high levels of callous-unemotional (CU) traits and relational victimization. Thus, the present study investigated sex differences in relational aggression, and associations between relational aggression and correlates of proactive aggression in 662 adolescents with CD (403 females) and 849 typically-developing controls (568 females) aged 9-18 years (M = 14.74, SD = 2.34) from the European multi-site FemNAT-CD study. Females with CD showed significantly higher levels of relational aggression compared to males with CD, whereas no sex differences were seen in controls. Relational aggression was only partly related to correlates of proactive aggression in CD: Independent of sex, CU traits showed a positive association with relational aggression. In females only, cognitive, but not affective empathy, was negatively associated with relational aggression. Relational victimization was more strongly associated with relational aggression in males compared to females. Despite interesting sex specific correlates of relational aggression, effects are small and the potential clinical implications should be investigated in future studies.
Gesehen am 19.11.2019